KV7 Channels Regulate Firing during Synaptic Integration in GABAergic Striatal Neurons - M. Belén Pérez-Ramírez; Antonio Laville; Dagoberto Tapia; Mariana Duhne; Esther Lara-González; José Bargas; Elvira Galarraga (Neural Plasticity)
Striatal projection neurons (SPNs) process motor and cognitive information. Their activity is affected by Parkinson’s disease, in which dopamine concentration is decreased and acetylcholine concentration is increased. Acetylcholine activates muscarinic receptors in SPNs. Its main source is the cholinergic interneuron that responds with a briefer latency than SPNs during a cortical command. Therefore, an important question is whether muscarinic G-protein coupled receptors and their signaling cascades are fast enough to intervene during synaptic responses to regulate synaptic integration and firing. One of the most known voltage dependent channels regulated by muscarinic receptors is the KV7/KCNQ channel. It is not known whether these channels regulate the integration of suprathreshold corticostriatal responses. Here, we study the impact of cholinergic muscarinic modulation on the synaptic response of SPNs by regulating KV7 channels. We found that KV7 channels regulate corticostriatal synaptic integration and that this modulation occurs in the dendritic/spines compartment. In contrast, it is negligible in the somatic compartment. This modulation occurs on sub- and suprathreshold responses and lasts during the whole duration of the responses, hundreds of milliseconds, greatly altering SPNs firing properties. This modulation affected the behavior of the striatal microcircuit.